EMPIRICAL EVALUATION OF GAMING SOFTWARE OF THE GAMIFICATION ENVIRONMENT FOR THE PREPARATION OF FUTURE BACHELORS OF INFORMATICS - Verbovetskyi, Dmytro; Oleksiuk, Vasyl (Journal of Information Technologies in Education (ITE), 2024)
The article presents a model of introducing a gamification environment into the educational process for the preparation of future bachelors of informatics. We have analyzed the domestic and foreign experience in selecting criteria for software and hardware, determined the criteria for selecting the components of the gamification environment and the indicators of each criterion, selected the components of the gamification environment, conducted an experimental evaluation of some software samples according to the defined criteria. Design, cloud-oriented, content and information and communication criteria were selected for the selected platforms and their components were outlined. A table of evaluation by experts was developed and the results were analyzed. A ranking of the received data was also made and conclusions were drawn based on the evaluation results. According to experts' assessments, the environment most suitable and least suitable for the selected criteria was determined, as it scored the highest and lowest number of points. The purpose of the article is to design a model of a gamification environment for training future bachelors of computer science in higher education institutions. We see the design of other components of the gamification environment, the creation of tasks using gamification technologies, the analysis of feedback, the development of technological infrastructure and the creation of methodological recommendations for the implementation and use of the environment as further perspectives of the research.